KONTRIBUSI DINDING BATA TERHADAP KINERJA STRUKTUR SPACE FRAME DENGAN METODE PUSHOVER (STUDI KASUS PADA GEDUNG IKATAN ALUMNI UNIVERSITAS SYIAH KUALA) - Agung Mardhika; Mochammad Afifuddin; Muttaqin Muttaqin (Prodi Magister Teknik Sipil Unsyiah, 2019)
The influence of brick walls to performance of space frame is often being ignored, even though in this condition walls are participating in strengthen the building. Contribution of brick walls to performance of space frame structure with push over method goal is to know how the impact of walls in building structure performance which is being ignored all this time. Building of alumnus association was being modeled in two condition, first condition with the walls were being ignored and second condition with brick walls were modeled as a strut force. Modeling brick walls as strut alumnus association building Syiah Kuala university increased structure performance at this building. Modelling with brick walls as strut in pushover analysis x direction at MTS model minimize the displacement 6,36% from MTS model and increased building ability to accept base shear 301,71% from MTS model. Modelling with brick walls as strut in analysis displacement at Y direction increase 4,38% from MTS model. This thing showed that walls impacted building performance in bearing base shear. Plastification condition structure element at X direction without strut modeling, there is 54 element which had already collapsed (greater than collapse prevention) whereas at building with strut modelling has 6 element which already collapsed (greater than collapsed prevention). Plastification condition element structure at Y direction in building without strut modelling has 14 element which already collapsed (greater than collapsed prevention).